Guidelines for Legislative Libraries. 2nd, completely updated and enlarged edition - Cuninghame, Keith (IFLA Publications, 2009)
The scale of change in the provision of information and research services since the original edition of this guide (published 1993), in particular the development of the Internet, meant that it soon became clear that a more or less complete re-write was needed, rather than simply a revision of the existing text. However, the new edition has kept to the spirit of the original, which has been a valuable tool for many.; Keith Cuninghame, former staff member of the UK House of Commons Library, London, Gro